Bullying: Forms, Factors, and Roles of Religion Teachers: (Case Study of Student SMAN 1 Astanajapura Kabupaten Cirebon) - Siti Maryam Munjiat; Iik Ahmad Taufik; Muthoharoh Muthoharoh (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
Bullying is one of the issues that persist today and has yet to be resolved because it is seen as a natural occurrence, even though it has both short- and long-term consequences for victims, offenders, and those who watch it. As a result, the purpose of this research is to identify the types of bullying that exist in SMAN 1 Astanajapura, Cirebon Regency, as well as the role of Religion Teachers in dealing with bullying in SMAN 1 Astanajapura, Cirebon Regency. At SMAN 1 Astanajapura, Cirebon Regency, and understanding the variables that lead to bullying. This sort of study combines qualitative and descriptive research methods. Observation, interviews, documentation using data reduction analysis, data presentation, and verification are all used in the data collection approach. The findings revealed that the most common form of bullying in SMAN 1 Astanajapura were verbal bullying, which included providing nicknames, mocking, and disparaging others' physical or mental flaws. Hitting, pinching, grabbing, and harassing are examples of physical bullying. Psychological bullying, such as ostracism, and media bullying, such as mocking on social media or in online games. Second, PAI teachers' role in dealing with bullying is divided into two stages: prevention and follow-up, which includes things like conducting supervision, socializing and extracurricular activities, guidance, teaching education and exemplary behaviour, and coordinating with all school members. Parents, friends, and social media were all contributors to the bullying that occurred at SMAN 1 Astanajapura.